Analisis Potensi Wilayah Kab, Batubara Dengan Tekhnik Lq (Location Quotient) Dan Shift Share - Rita Handayani (CERED Indonesia Institute, 2023)
LQ analysis is used to measure the level of specialization of the economic sector in the coal region, while Shift Share analysis is used to analyze the contribution of internal and external factors to changes in the performance of the economic sector. In the results and discussion, LQ and Shift Share calculations were carried out using GRDP data from coal districts and North Sumatra province. The results of the LQ analysis show economic sectors that form a strong economic basis in the coal region. Meanwhile, the results of the Shift Share analysis help identify factors that influence growth and changes in economic sectors in the coal region. This research contributes to optimizing the economic potential of the coal region and encouraging sustainable economic growth through a better understanding of the economic basis and factors that influence the growth of economic sectors within it. The results of this research are also useful for policy makers, entrepreneurs and other stakeholders in identifying investment opportunities and potential economic sector development in the coal region..